Investigation on the influence of tool wear upon chip morphology in end milling titanium alloy Ti6Al4V. Issue 9 (April 2016) - Zhu, Zhaoju; Sun, Jie; Li, Jianfeng; Huang, Panling
Abstract Titanium alloys are widely utilized in aerospace, automotive, biomedical and chemical engineering, etc., thanks to their excellent combination of high-specific strength, fracture, corrosion resistance characteristics, etc. However, titanium alloys are difficult-to-machine materials. Tool wear is one of the bottlenecks restricting their machining efficiency. A systematic study on the relationships among tool wear, chip morphology, and cutting vibration is inadequate. In this study, chip morphology and cutting vibration characteristics under different tool wear stages are examined using optical microscope, SEM, and vibration test system. The mechanism of tool wear in end milling titanium alloy is also investigated. Results indicate that with the progression of tool wear, the chip segment degree becomes more and more serious. The mechanism for this phenomenon is probed. Tool wear progression enlarges the cutting vibration which causes the friction force on tool/chip interfaces to increase, and this aggravates chip edge wear accordingly. On the contrary, the increase of chip segment degree induces the progression of cutting vibration and tool wear. Therefore, the aim of the present research is to investigate the sophisticated relationship. This will benefit for improving cutting efficiency and guaranteeing machining quality in end milling titanium alloy.